Life satisfaction among women in Sabah, Malaysia: a quantitative study - Elpidia Juli,; Md Sayed Uddin,; Trixie Marjorie Tangit, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Life satisfaction in Malaysia is influenced by socio-demographics such as marital status, age, gender, religiosity, ethnicity and geographical area. However, there is also additional external factor that influenced women’s life satisfaction which is work-life conflict. This study aims to investigate women’s work-life conflict in relation to their life satisfaction based in Kota Kinabalu, Sabah, Malaysia. Secondly, this study also investigates women’s level of life satisfaction in Sabah, Malaysia. A quantitative research design by using self-administered questionnaire via online Google Form and physical hand-in was used to answer the research objectives. A total of 348 female respondents have voluntarily participated in the study that work in government institutions, by using convenience sampling method. Based on findings, work-life conflict has negatively correlated with a strong correlation of -0.373 towards life satisfaction and vice versa. In addition, female respondents’ level of life satisfaction is overall between neutral. This study offers new insights where one of insights is women in Sabah, Malaysia, especially female government servants feel unsure whether that they are highly satisfied in life, especially individuals in the mid 30’s and above.